Approach to the coughing dog. Issue 9 (4th October 2013) - Martin, Mike; Pereira, Yolanda Martinez
Abstract : A wide variety of conditions can cause coughing in dogs, which can present either as an acute problem or a chronic condition. This article aims to provide a pragmatic review of coughing in dogs. An understanding of the location of the cough receptors in the respiratory tract is key to understanding how best to investigate coughing. It considers the pathophysiology of coughing and its diagnosis, offering tips on the more useful diagnostic tests for each condition.